O modelo referencial da linguagem na tradução-interpretação da linguagem matemática pelos surdos usuários da Libras - COSTA, Walber Christiano Lima da (Universidade Federal do Pará, 2021)
This thesis presents a study about the use of Referential Model of Language in the translation-interpretation of mathematical language by the deaf users of Libras. This study aims to: inves- tigate the influences of the use of the Referential Model of Language by deaf students in the learning of mathematics; analyze the translation processes of deaf students in mathematics classes; investigate the language games in the use of several languages in the context of the learning by deaf students. To this end, we rely on some concepts of Wittgenstein's philoso- phy, as well as on mathematical educators who join hisideas to think teaching and on authors discussing inclusive education. We support the hypothesis that, when translating mathemati- cal concepts into Libras, deaf students make use of the Referential Model of Language, which reach for the word-for-word translation or signal word. And our thesis is: the referential use of language prejudices learning in mathematics by deaf students, since it’s been noticed that deaf students make translations that do not express the meanings of the mathematical text. We conducted a field research in two cities in the State of Pará, with a total of 13 deaf students, four at one school and nine at a second one. For data collection and analysis, we have created a class with deaf students in each school. We chose to build up such classes because of our focus on deaf students and their translations. Considering the qualitative approach, we realize that deaf students use the literal translation that stems from the Referential Model of Lan- guage, in other words, a word-sign translation, making them unable to understand mathemati- cal concepts. By employing it this way, deaf students use a language game that is not what the teacher proposes in the classroom. And this corroborates to a scenario of exclusion, which would goagainst the ideas of inclusion,fair education and quality to all. We assume that lin- guistic differences often cause disturbance, since there are still scenarios without the presence of fluent teachers in Libras and no professional translator-interpreters and, along with the use of referentiality, end up bringing even more difficulties to the deaf. We have noticed in the field research that even deaf students in more advanced grades experience difficulties in the translation-interpretation of mathematical texts, what evidences the harm that this Model brings to the learning, in mathematics, by deaf students.